Sistemi di scarico articolare extra-capsulari del ginocchio: stato dell’arte - Zedde, P.; Uboldi, F.M.; Denti, F.; Puddu, L.; Cudoni, S. (Lo Scalpello - Journal, 2019)
EXTRA-CAPSULAR KNEE JOINT UNLOADING IMPLANT SYSTEM: STATE OF THE ART The treatment of early osteoarthritis of the knee can also be addressed with the use of different techniques that provide for the discharge of the affected joint compartment. Internal extra-articular devices consist of metal or polycarbonate-urethane shock absorbers fixed to the femur and tibia by angular stability plates. Their purpose is to unload the joint and allow for reduction of the intra-articular compressive strength in the first degrees of flexion without modifying its anatomy and biomechanics and, therefore, being reversible. The literature is lacking in medium- and long-term clinical results with the presence of limited case series or case reports with contrasting results that do not provide significant conclusions on their efficacy but highlight some complications. Further studies are needed, as the theory is very promising.